A DENSITY FUNCTIONAL THEORY (DFT) STUDY ON SILICON DOPED CARBON NANOTUBE Si-CNT AS A CARRIER FOR BMSF-BENZ DRUG USED FOR OSTEOPOROSIS DISEASE - Al-Sawaff, Zaid H.; Senturk Dalgic, Serap; Kandemirli, Fatma (MOMENTO, 2022)
This study aims to investigate the capability of Silicon-Doped Carbon Nanotube (Si-CNT) to detect and adsorb the BMSF-BENZ ((4-Bromo-7-methoxy-1-(2-methoxyethyl)-5-{[3-(methylsulfonyl)phenyl]methyl}-2-[4- (propane-2-))yl)phenyl]-1H-1,3-benzothiazole) molecular. For this purpose, we considered different configurations for adsorbing BMSF-BENZ drugs on the surface of the Si-CNT nanotube. All considered configurations are optimized using the density functional theory (DFT) at the 6-31G∗∗ basis set and B3LYP-B97D level of theory. Then from optimized structures, for each nanoparticle, we selected seven stable locations for the adsorption of BMSF-BENZ in (Br, N8, N9, N58, O35, O41 and S) active atoms on the surface of the selected nanoparticle. The quantum theory of atoms in molecules (QTAIM), reduced density gradient (RDG) analysis, and molecular orbital (MO) analysis were also established. The calculated results indicate that the distance between nanotube and drug from the N8 site is lower than from all other locations sites for all investigated complexes, and adsorption of BMSF-BENZ from the N8 site is more favorable for the Si-CNT nanotube. The adsorption energy, hardness, softness, and fermi energy results reveal that the interaction of BMSF-BENZ with Si-CNT is a promising adsorbent for this drug as Adsorption energy Eads of BMSF-BENZ/Si-CNT complexes are (-13.08, -43.50, -17.90, -31.29, -25.57, -16.56, and -28.05) kcal/mol in the gas phase. As well, the appropriate and spontaneous interaction between the BMSF-BENZ drug and Si-CNT nanoparticle was confirmed by investigating the quantum chemical molecular descriptors and solvation Gibbs free energies of all atoms.